KREATIV FIKRLASHNING IJTIMOIY YORDAMCHI OMILLARI - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2022)
Creative Thinking Indicators Ensure students’ creativity in assignments where much of the creative thinking process is invisible. The creative product depends on the social context, and this social context is shaped by cultural norms and expected outcomes